A STUDY OF ECOLOGICAL ARCHITECTURE CONCEPTS IN THE RESIDENCE OF GLINTUNG VILLAGE, MALANG CITY - Larasati, Rezka Ajeng; Satwikasari, Anggana Fitri (Talenta Publisher, 2022)
Settlement is one of the urban development variables which has an important role in urban development. Urban development will always face various problems, especially those caused by settlements. These problems are related to the construction of settlements that are not in harmony with their environmental ecosystem. Based on these issues, ecological architecture is one of the architectural sciences that can be applied in planning and designing residential areas. This research was conducted with the aim of understanding and identifying the application of the principles of ecological architecture in a settlement. The research method used is descriptive qualitative method with primary data in the form of interview-related interviewees and secondary data in the form of literature studies. The analysis was carried out based on the ecological architectural variables which were arranged systematically. The study of the concept of ecological architecture was carried out in a settlement that has attempted to apply several principles of ecological architecture. The residential area is Kampung Glintung, a city known as Kampung Kultur or Kampung 3G (Glintung Go Green). The preparation of this research is expected to provide an understanding of the concept of ecological architecture and provide an overview of the importance of planning and designing environmental-based residential areas to support urban survival and the people who live in it. Keywords: settlement, ecology, ecological architecture, urban development, environmental ecosystem